PERBAIKAN SISTEM KERJA BERDASARKAN ASPEK BIOMEKANIKA DI PT. CRESCO INDONESIA - Norina, Rida; Adriyanti, Erina (Teknik Industri Unikom, 2021)
PT. Cresco Indonesia is one of the companies that concerned in the Japanese slipper sandals industry in West Java, which was established in 1989. In order to responses to demanding costumer, PT. Cresco Indonesia applies ‘make to order’ strategy, so the production process will be carried out if there are any orders from consumers. The company has 13 departments. Based on observations has known that there are 4 departments that have a potential to cause an accidents work, they are the happo department, the shiage department, the quality control department and the packing department. The beginning measurements of RULA and REBA out of four departments show the results of high risk action levels. To improve the situation, work system improvements must be made. This study intends to improve the body's posture and work system currently, so that the design of tools for the movement of baskets in the shiage and quality control departments, grouping and labeling in baskets in the happo department as well as improve the order of the process of lifting goods in the packing department. Work system improvement is carried out using biomechanics theory. The final result of the design shows the value of RULA and REBA of operators is low risk, minimizes the value of defects in the happo department, reduces the activities of finding baskets in the happo department, minimizes the time of movement from the shiage department to the quality control department, improves the way of lifting goods in the packing department and fix up the posture of the operators